Analysis of ground reaction forces in the second and third trimesters of pregnancy during walking (Kinesiology, 2019)
The objective of the current study was to examine the effect of pregnancy during the 2nd and 3rd trimesters on ground reaction forces (GRFs). Twenty-four non-pregnant women and forty-eight pregnant women in the second and third trimesters participated in this cross-sectional study. Qualysis Gait Analysis System was used to analyze peaks and time parameters of GRFs in vertical (Fz), antero-posterior (Fx) and medio-lateral directions (Fy). The results showed that there were no significant differences between non-pregnant and pregnant women in the first peak (Fz1) (p=0.147) and second peak (Fz2) (p=0.125) of vertical GRF, braking force (FxB) (p=0.867) and propulsion force (FxP) (p=0.929), as well as lateral (FxL) (p=0.994) and medial (FxM) GRF (p=0.920). However, there was a significant decrease in the Fz minimum (min) (p=0.008), the difference between the Fz1 and Fz min (p=0.042) and the difference between Fz2 and Fz min (p=0.028). Moreover, there were increases in the time taken to reach the Fz1 (p=0.024), Fz2 (p=0.005), Fz min (p=0.001), FyB (p=0.010), FyP (p=0.001), FxL (p=0.010) and FxM (p=0.011). These findings displayed that the pregnant women assumed flatter pattern of vertical GRF and decreased upward and downward movement of center of gravity. This pattern may help to make the gait smooth and efficient. Increased time to reach peaks of GRFs may be a strategy to maximize balance during pregnancy.